Ficções e dicções pós-antropofágicas na cena literária brasileira contemporânea - Silva, Nádia Regina Barbosa da (2006)
Post-anthropophagic Fictions and Dictions in Contemporary Brazilian Literary Scene aims at examining the extent to which the formal and thematic implications of fictional language at the turn of the 20th to the 21st century with a variety of dictions that impose themselves on the Brazilian literary scene today illuminate issues concerning today s subjectivity and contribute to the debate on this subject and, therefore, shed light on Brazilian history. This investigative task privileges the comparison between the fictional text and a collection of extraliterary particularities that give shape to the time in which we live. The literary text, object of this study, albeit performing a central role, never does so in an isolated way, since today it is possible to realize the fact that the artistic text constitutes, and affirms itself as, a dialogical space of heterogeneity, a space in which many points of intersection are created between the literary text itself and other texts and between this kind of art and other aesthetics theatre, cinema, photography, etc. that are added to present day theories: a site, therefore, where various language expressions co-exist. At the end of this research, a rich production that points beyond modernism is found, referred to in this thesis as post-anthropophagic, consonant with the contemporary Brazilian historical moment whose aesthetic requirements claim for a new model, unattached from the European one, not submitted to international modernity.